2021
DOI: 10.1158/2767-9764.crc-21-0033
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 Inhibition Blocks Adaptive Resistance and Synergizes with MEK Inhibition for the Treatment of NRAS-Mutant Melanoma

Abstract: NRAS-mutant melanoma is currently a challenge to treat. This is due to an absence of inhibitors directed against mutant NRAS, along with adaptive and acquired resistance of this tumor type to inhibitors in the MAPK pathway. Inhibitors to MEK have shown some promise for NRAS-mutant melanoma. In this work, we explored the use of MEK inhibitors for NRAS-mutant melanoma. At the same time, we investigated the impact of the brain microenvironment, specifically astrocytes, on the response of a melanoma brain metastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Western blot analysis revealed that ferroptotic cell death is characterized by a marked loss of many proteins, including several with roles in ferroptosis, such as GPX4 and ACSL4 (acyl-CoA synthetase long-chain family member 4; Figure B, Figure S1B and C). These changes closely resemble those caused by an inhibitor of the stress-inducible molecular chaperone HSP70 (Figure C). As shown (Figure S1D), treating cells with the HSP70 inhibitor AP-4-139B (hereafter 139B) , results in a similar dose-dependent cytotoxicity in all melanoma cell lines examined, regardless of genotype or differential ferroptosis sensitivity.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Western blot analysis revealed that ferroptotic cell death is characterized by a marked loss of many proteins, including several with roles in ferroptosis, such as GPX4 and ACSL4 (acyl-CoA synthetase long-chain family member 4; Figure B, Figure S1B and C). These changes closely resemble those caused by an inhibitor of the stress-inducible molecular chaperone HSP70 (Figure C). As shown (Figure S1D), treating cells with the HSP70 inhibitor AP-4-139B (hereafter 139B) , results in a similar dose-dependent cytotoxicity in all melanoma cell lines examined, regardless of genotype or differential ferroptosis sensitivity.…”
Section: Resultssupporting
confidence: 55%
“…These changes closely resemble those caused by an inhibitor of the stress-inducible molecular chaperone HSP70 (Figure C). As shown (Figure S1D), treating cells with the HSP70 inhibitor AP-4-139B (hereafter 139B) , results in a similar dose-dependent cytotoxicity in all melanoma cell lines examined, regardless of genotype or differential ferroptosis sensitivity. RSL3-mediated ferroptosis leads to an increase in ferrous iron and MDA (Figure S1E), which is a toxic product of lipid peroxidation; 139B-mediated HSP70 inhibition had little effect on these factors (Figure S1E).…”
Section: Resultsmentioning
confidence: 99%